TAX HAVENS – FEATURES, OPERATIONS AND SOLVING TAX EVASION PROBLEMS - Obradović Ćuk, Jelena M; Mitić, Petar D; Dinić, Vladimir (International Journal of Economic Practice and Policy, 2017)
Tax haven offers minimal or no tax liability to foreign individuals and enterprises in economically and politically stable environment, where little or no financial information is shared with foreign tax authorities. The aim of this research is to create a comprehensive overview of the characteristics and operations of tax havens, as well as to point out to the ways to overcome the problem of tax evasion. The methodology used in the work is characteristic of social science research: analysis, synthesis and discussion, comparative, inductive and historical analysis, together with the usage of relevant national and international sources. This paper describes the basic features of tax havens, as well as specific business models applied in them. A separate chapter deals with overcoming the problem of tax evasion, which is the main adverse effect of doing business through tax havens..